Preserving traditional healing: some political questions - Dandekar, Deepra (Economic & political weekly, 2014)
Priests and mediums associated with "healing" folk cults have also been viewed as empowered agents of alternative modernity, and outside the priest's caste or class-based social context. In reality, the healer is often poor, and belongs to a lower caste. He or she is subject to the demands of the upper caste, rich clans, while ritually diagnosing the ailments of the latter's dependents in return for financial and political support.
Gesehen am 21.04.2020